Photocontrol in Complex Polymeric Materials: Fact or Illusion?. Issue 27 (4th June 2018) - Jerca, Valentin Victor; Hoogenboom, Richard
Abstract : Photoswitches : Exciting recent progress realized in the field of light‐controlled polymeric materials is highlighted. It is discussed how the rational choice of azobenzene molecules and their incorporation into complex materials by making use of physical interactions can lead to genuine photocontrollable polymeric systems.